Public relations in health and medicine: using publicity and other unpaid promotional methods to engage audiences - James K. Elrod; John L. Fortenberry (BMC, 2020)
Abstract Background Public relations-a marketing communications method involving the use of publicity and other unpaid promotional methods to deliver messages-historically has served as the communicative workhorse of the health services industry, representing the predominant pathway over many decades by which health and medical facilities conveyed stories to the public. While other components of the marketing communications mix, perhaps most notably that of advertising, have now captured a significant portion of interest, attention, and use by healthcare establishments, public relations remains a valuable communicative avenue when deployed properly. Discussion As an unpaid method of promotion, public relations is uniquely positioned among its counterparts in the marketing communications mix which require direct expenditures to reach audiences. Typically effected by preparing and submitting press releases to news media firms in hopes that they, in turn, will present given stories to their audiences, limitations are somewhat obvious as transmission control rests with external entities. But overcoming limitations is possible with prudent strategies. This article presents Willis-Knighton Health System's associated strategies, along with a range of public relations insights from decades of deployment experience. Conclusions Prudently deployed and led by guiding strategies, public relations offers health and medical organizations opportunities to engage audiences in an efficient and highly credible manner. Courtesy of its unique properties, public relations capably can complement other marketing communications, operating synergistically to help healthcare institutions achieve their conveyance goals, fostering exchange and bolstering market share. Careful operationalization of this marketing communications avenue can help healthcare establishments realize their full communicative potential.